Mapping strengths into virtues: the relation of the 24 VIA-strengths to six ubiquitous virtues - Ruch, Willibald; Proyer, René T. (Frontiers in Psychology, 2015)
The Values-in-Action (VIA)-classification distinguishes six core virtues and 24 strengths. As the assignment of the strengths to the virtues was done on theoretical grounds it still needs empirical verification. As an alternative to factor analytic investigations the present study utilizes expert judgments. In a pilot study the conceptual overlap among five sources of knowledge (strength’s name including synonyms, short definitions, brief descriptions, longer theoretical elaborations, and item content) about a particular strength was examined. The results show that the five sources converged quite well, with the short definitions and the items being slightly different from the other. All strengths exceeded a cut-off value but the convergence was much better for some strengths (e.g., zest) than for others (e.g., perspective). In the main study 70 experts (from psychology, philosophy, theology, etc.) and 41 laypersons rated how prototypical the strengths are for each of the six virtues. The results showed that 10 were very good markers for their virtues, 9 were good markers, four were acceptable markers, and only one strength failed to reach the cut-off score for its assigned virtue. However, strengths were often markers for two or even three virtues, and occasionally they marked the other virtue more strongly than the one they were assigned to. The virtue prototypicality ratings were slightly positively correlated with higher coefficients being found for justice and humanity. A factor analysis of the 24 strengths across the ratings yielded the six factors with an only slightly different composition of strengths and double loadings. It is proposed to adjust either the classification (by reassigning strengths and by allowing strengths to be subsumed under more than one virtue) or to change the definition of certain strengths so that they only exemplify one virtue. The results are discussed in the context of factor analytic attempts to verify the structural model.